Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s11845-009-0327-3
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset CMV disease following CMV prophylaxis

Abstract: The incidence of CMV infections in this study was low compared with literature reports; however, the late-onset disease is an emerging problem. Detection of late-onset disease may be delayed because of less frequent clinic follow-up visits. Increased regular laboratory monitoring may allow earlier detection at the asymptomatic infection stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 13 publications
2
16
1
Order By: Relevance
“… 15 Dollard and colleagues 15 found that the overall prevalence of congenital CMV infection in industrialized countries is likely to be 0.6% to 0.7% which the authors state is more precise than the range of 0.2% to 2.5% often cited in the literature. Another study in agreement with our findings reported that the incidence of CMV infection and CMV disease were low in a cohort of Irish liver transplant recipients 16 compared with the published literature. 17 , 18 However, future studies in other countries are required to confirm this association and to address the strong selection pressure which HLA genes are under due to mechanisms such as selection, mutation, genetic drift but in particular migration.…”
Section: Discussionsupporting
confidence: 93%
“… 15 Dollard and colleagues 15 found that the overall prevalence of congenital CMV infection in industrialized countries is likely to be 0.6% to 0.7% which the authors state is more precise than the range of 0.2% to 2.5% often cited in the literature. Another study in agreement with our findings reported that the incidence of CMV infection and CMV disease were low in a cohort of Irish liver transplant recipients 16 compared with the published literature. 17 , 18 However, future studies in other countries are required to confirm this association and to address the strong selection pressure which HLA genes are under due to mechanisms such as selection, mutation, genetic drift but in particular migration.…”
Section: Discussionsupporting
confidence: 93%
“…The use of prophylaxis against CMV infection has reduced the incidence of early CMV infection/disease in pediatric population. However, late CMV infection or disease post‐prophylaxis is an emerging problem in the pediatric population and is also well documented in adult LT recipients . The overall incidence of late CMV infection in our series was significantly higher at 10.5% in comparison with 6% reported by Honar et al.…”
Section: Discussioncontrasting
confidence: 59%
“…In most of the adult studies and in a retrospective review of 93 PLTR, D−R+ group was considered as a low‐risk group for acquiring CMV‐associated complications . The association between CMV infection and graft rejection after LT is well known . This association has been commonly reported in the high‐risk D+R− group after stopping prophylaxis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this systematic review and meta‐analyses, we included randomized controlled trials (RCTs) and observational studies in LTRs reporting on GCV or VGCV for UP and/or PE regardless of the language in which they were published. We excluded studies that used shell vial culture technique for CMV detection, as well as those reporting only on late CMD (beyond the first year of LT) .…”
Section: Methodsmentioning
confidence: 99%